(3GdJNWjW GdGSJQGJjLj (B/s - (3UbQ, fHjd MGeO eQSjs ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2008)
(3jVe NUGFU fXGe GdJNWjW GdGSJQGJjLj, GdQDjI hGdQSGdI , CfhGY GdCgOGa defXeGJ GdCYeGd, eaghe GdHjFI GdeMjWI HGdefXeI, JMdjd GdHjFI GdJfGaSjI, JMdjd ChLg GdbhI hGdVYa GdOGNdjI, HYV GdCOhGJ GdJMdjdjI GdJj JSJNOe aj GJNGP GdbQGQGJ GdGSJQGJjLjI, CfhGY GdHOGFd GdGSJQGJjLjI, KbGaI GdefXeI, EYOGO Gdgjcd GdJfXjej, GdbjGOI GdGOGQjI, EOGQI GdLhOI GdTGedI ceONd dESJQJjLjI GdJWhjQ GdJfXjej, GSJQGJjLjI GdNUNUI(B"(3GdJLQHI GdeUQjI(B" (3, GdJNWjW Gdbhejs
(3GdeQGLY U(B.327s
Keywords: (3EJNGP GdbQGQGJ(B- (3GdEOGQIs; (3EOGQI GdCYeGds; (3GdJNWjWs; (3GdJNWjW (B- (3JfXje hEOGQIs